Troceado de madera tropical mediante harvester y su impacto en el nivel de rendimiento y costo, año 2015. Propuesta de modelo de cosecha. - Aguilar Romero, Fernando Fabián (2016)
The present study to assess the impact of tropical wooden chopping through Harvester level of performance and cost according to the research question for registration of species, measurement and estimation of the independent variables (Tropical wood chopped) indicators per unit of sampling were used: Diameter (DAP, larger diameter and smaller diameter) and height (total height and commercial height) stem volume (Vf), total trade volume (Vc) of individuals and species. The measurement of the dependent variable (performance (m3 h-1) and cost (m3) cutting of tropical timber) is required of all 5 species Cedrelinga cateniformis (Chuncho), Parkia multijuga (Cutanga), Jacaranda copaia (Jacaranda), Cordia alliodora (Laurel) and Terminalia ivorensis (Terminalia). The two species Jacaranda copaia and Terminalia ivorensis were the best performing m3 h-1 and cost. Forest Inventory more species Vc/ha of 2.65 m plots are Cedrelinga cateniformis and Terminalia ivorensis, with 201m3 h-1 and 252m3 h-1, the plots are 5.35 m Cedrelinga cateniformis and Terminalia ivorensis with 212m3 h-1 and 302m3 h-1, the study of time logs of 2.65 m two species Jacaranda copaia was obtained, and Terminalia ivorensis with shorter chopped 41 minutes and 43 minutes due to self pruning silvicultural management tree and study time logs 5.35 m two species Cordia alliodora was obtained, and Parkia multijuga, with shorter chopped 29 minutes and 32 minutes due to silvicultural management knotless clear bole. With regard to performance m3 h-1 was cutting costs for logs of 2.65 m two species Jacaranda copaia was obtained, and Terminalia ivorensis with 0.94 cents and 0.73 cents and time study 5.35 m logs of two species Jacaranda copaia and Terminalia ivorensis with 0.71 cents and 0.54 cents was obtained. Depending on the results a proposal that is oriented on a model of tropical wood harvesting are of great importance for forest harvesting was developed.